Five Years Follow-up of Opsoclonus–Myoclonus–Ataxia Syndrome-Associated Neurogenic Tumors in Children - Aktekin, Elif Habibe; Gezer, Hasan Özkan; Yazıcı, Nalan; Erol, İlknur; Erbay, Ayşe; Sarıalioğlu, Faik (Neuropediatrics, 2023)
Aim Opsoclonus–myoclonus–ataxia syndrome (OMAS) is a rare autoimmune disorder. Approximately half of the cases are associated with neuroblastoma in children. This study's aim is to review management of our cases with OMAS-associated neuroblastoma for treatment approach as well as long-term follow-up.Methods Age at onset of symptoms and tumor diagnosis, tumor location, histopathology, stage, chemotherapy, OMAS protocol, surgery, and follow-up period were evaluated retrospectively in six patients between 2007 and 2022.Results Mean age of onset of OMAS findings was 13.5 months and mean age at tumor diagnosis was 15.1 months. Tumor was located at thorax in three patients and surrenal in others. Four patients underwent primary surgery. Histopathological diagnosis was ganglioneuroblastoma in three, neuroblastoma in two, and undifferentiated neuroblastoma in one. One patient was considered as stage 1 and rest of them as stage 2. Chemotherapy was provided in five cases. The OMAS protocol was applied to five patients. Our protocol is intravenous immunoglobulin (IVIG) 1 g/kg/d for 2 consecutive days once a month and dexamethasone for 5 days (20 mg/m2/d for 1–2 days, 10 mg/m2/d for 3–4 days, and 5 mg/m2/d for the fifth day) once a month, alternatively by 2-week intervals. Patients were followed up for a mean of 8.1 years. Neuropsychiatric sequelae were detected in two patients.Conclusion In tumor-related cases, alternating use of corticosteroid and IVIG for suppression of autoimmunity as the OMAS protocol, total excision of the tumor as soon as possible, and chemotherapeutics in selected patients seem to be related to resolution of acute problems, long-term sequelae, and severity.
Keywords: opsoclonus–myoclonus–ataxia syndrome; neuroblastoma; immunosuppression; tumor; surgery; sequelae